2011
DOI: 10.1200/jco.2011.29.27_suppl.1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation of breast cancer: Age, stage, and treatment modalities in a contemporary cohort of Michigan women.

Abstract: 1 Background: The U.S. Preventative Services Task Force (USPSTF) revised their breast cancer screening recommendations in 2009 changing their stance on age and frequency of mammography screening to biannual exams starting at age 50. The purpose of this study is to analyze data from a statewide breast cancer registry managed by the Michigan Breast Oncology Quality Initiative (MiBOQI) to determine the impact of these new recommendations on diagnosing and treating breast cancer. Methods: De-identified data were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Some other study found that breast cancer with an average age at diagnosis of 59.4 years. 6 Another study showed that age range was 18 to 82 years, with a mean of 45.17 years. 7 This study showed that maximum patients i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Some other study found that breast cancer with an average age at diagnosis of 59.4 years. 6 Another study showed that age range was 18 to 82 years, with a mean of 45.17 years. 7 This study showed that maximum patients i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The timeliness benchmark for surgery measures initiation of surgery within 45 days of the initial diagnosis for patients with surgery recommended as the first treatment. 21,22 The benchmark of adjuvant hormone treatment measures initiation of hormone therapy within 1 year of diagnosis in stage I to III hormone receptorpositive patients 18 years of age and older. The total number (N) and the percentage of evaluable cases meeting and not meeting each benchmark (%) were reported.…”
Section: Discussionmentioning
confidence: 99%
“…8,10 Many efforts have been made to eliminate delay-related breast cancer disparities, particularly for early stage disease, including establishment of quality benchmarks by several disease-specific consortia and government agencies, such as the National Quality Forum (NQF) [17][18][19][20] and the Michigan Breast Oncology Quality Initiative (MiBOQI). 21,22 Although the timeliness benchmarks have been established for years, few studies have evaluated how current breast cancer care meets these benchmarks. Furthermore, factors associated with meeting the timeliness benchmarks also remain unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation